-6=10(8+w)+3

Simple and best practice solution for -6=10(8+w)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=10(8+w)+3 equation:



-6=10(8+w)+3
We move all terms to the left:
-6-(10(8+w)+3)=0
We add all the numbers together, and all the variables
-(10(w+8)+3)-6=0
We calculate terms in parentheses: -(10(w+8)+3), so:
10(w+8)+3
We multiply parentheses
10w+80+3
We add all the numbers together, and all the variables
10w+83
Back to the equation:
-(10w+83)
We get rid of parentheses
-10w-83-6=0
We add all the numbers together, and all the variables
-10w-89=0
We move all terms containing w to the left, all other terms to the right
-10w=89
w=89/-10
w=-8+9/10

See similar equations:

| 50x+150=450 | | 3m+6=-7+4 | | 2x+5x=40+9 | | 15=y/4+13 | | 17x+5=80 | | 3.6y=5.4+3.3y,y= | | 6x+11=25=6 | | -3x+6+2x=9x-2x-2 | | 6-x7=5x3-2 | | 2(8u+2)=3(2u+7) | | 6+2(2u-1)=-5(2u-2)+6u | | 2n+2=3n+9 | | 13(4x-6)=23-6x | | 5=-6+x/3 | | 6+2(2u-1)=-5 | | 3(9-x)=6(x+6) | | (2x-60)+(3x+30)=180 | | 9/8=g+4/8 | | 4(7-n)=5n-8 | | -9.1(-7r-20)=-13 | | 3x=+4=-11 | | 3(y+2+2(y-3=15 | | 2(x5)-8=34 | | 12=y-5/4. | | Z+40=5z | | -9x+3=-10+10 | | -2h+4h=18 | | 120.5=5z. | | 0.15+23=0.19x | | t-7+3t=-2+4t-5 | | 5y-6=y+42 | | -2h+4=18 |

Equations solver categories